Pengelolaan Kinerja Kepala Sekolah melalui Optimalisasi Pendampingan Akademik: Upaya Peningkatan Mutu Pendidikan di Sekolah - Juhadira, Juhadira; Nasir, Nasir; Deluma, Ridwan (Magister Administrasi Pendidikan, Universitas Muhammadiyah Kendari, 2024)
This study explores the roles of vision, mission, and academic supervision in improving the quality of education at kindergartens (TK) in Kendari City. Interviews with school principals and observations reveal that vision and mission play strategic roles in guiding educational activities. Various kindergartens' visions include character development, local culture, and STEAM approaches, while missions outline concrete steps to achieve these visions. Academic supervision showed varied results, with TK Negeri 1 and TK Negeri 4 demonstrating high effectiveness due to constructive feedback and clear goals. In contrast, TK Negeri 2 and TK Nur Ichsany face challenges related to time efficiency and the development of evaluation instruments. Effective academic supervision contributes to improving teaching quality and student learning outcomes, although some areas require improvement for optimal efficiency. Innovative strategies, such as empowering teachers through additional training and coaching, as well as regular monitoring, are identified as key to creating a supportive learning environment. These findings support educational management theory emphasizing the importance of vision, mission, and supervision in early childhood education, and highlight the need for a holistic approach to enhancing education quality at kindergartens in Kendari.